Multi-site Information Synchronization Scheme Based on Wavelet Transform to Detect Signal Singularity - Baojiang TIAN; Yan LI; Xiaoyu LIAO; Xingwei DU; Wenyan DUAN (Zhongguo dianli)
The recording files of different devices in the substation are affected by the loss of synchronization signals and damage of communication channels, resulting in asynchronous recording files. However, various main protections such as longitudinal differential protection and distance protection in the power system, as well as secondary equipment such as merging units, phasor measurement units, and recorders used for fault analysis, have strict requirements for information synchronization. To address this issue, this article proposes a self synchronization scheme for recording files of different devices in substations based on the sudden variable detection algorithm. Firstly, considering the problems of high-frequency signal loss and boundary effects in the traditional Mallat wavelet algorithm, which affect the accuracy of mutation point detection, a complementary adjacent window algorithm and an optimization strategy for data window selection are proposed, effectively solving the problems of traditional wavelet transform. On this basis, a substation information synchronization scheme based on the improved Mallat wavelet algorithm is proposed. Finally, the feasibility and advantages of the proposed improved algorithm and the information synchronization scheme were verified through on-site analysis of the actual recorded wave data.